2013
DOI: 10.1007/s00774-013-0434-0
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated RNA interference of DC-STAMP expression inhibits the fusion and resorptive activity of human osteoclasts

Abstract: Cell-cell fusion is a critical step in osteoclast development, because only after osteoclasts become multinucleated can they efficiently resorb bone. Although recent studies suggest that dendritic cell-specific transmembrane protein (DC-STAMP) may play a key role in the process of fusion of mouse osteoclasts, little information has been available on the role of DC-STAMP in human osteoclasts. In this study, we screened and identified an in vitro-transcribed short-hairpin RNA targeting human DC-STAMP from four c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Bone diseases caused by excessive osteoclast activity such as osteoporosis and erosive arthritis can be moderated or prevented by medications that block DC‐STAMP activity. To date, miRNA (Sissons et al, ; Bernard, ; Dou et al, ; Chen et al, ) and RNA interference (Zeng et al, ) have been shown to effectively block the biological activity and gene expression of DC‐STAMP. In addition, since ITIM was present in the cytoplasmic tail of DC‐STAMP, employing ITIM‐bearing peptides to saturate and block DC‐STAMP‐interacting proteins remain an option to control DC‐STAMP function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bone diseases caused by excessive osteoclast activity such as osteoporosis and erosive arthritis can be moderated or prevented by medications that block DC‐STAMP activity. To date, miRNA (Sissons et al, ; Bernard, ; Dou et al, ; Chen et al, ) and RNA interference (Zeng et al, ) have been shown to effectively block the biological activity and gene expression of DC‐STAMP. In addition, since ITIM was present in the cytoplasmic tail of DC‐STAMP, employing ITIM‐bearing peptides to saturate and block DC‐STAMP‐interacting proteins remain an option to control DC‐STAMP function.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of DC‐STAMP at both mRNA and protein levels can be significantly and specifically inhibited by RNAi (Zeng et al, ). Of note, DC‐STAMP inhibition by RNAi consequently suppressed fusion and bone resorption of human osteoclasts, suggesting that inhibition of DC‐STAMP by RNAi is an efficient and effective method of regulating osteoclast functions.…”
Section: Regulators That Affect Dc‐stamp Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein has been shown to be expressed in dendritic cells and macrophages but predominantly in osteoclasts [34]. RNA interference studies on human osteoclasts demonstrated an essential role for osteoclastic cell–cell fusion and resorptive activity [28]. DC-STAMP-deficient mice did not develop multinucleation of osteoclasts [35].…”
Section: Introductionmentioning
confidence: 99%
“…The activities of these transcription factors consequently regulates osteoclast differentiation by upregulating the expression of osteoclast-associated genes, such www.nature.com/aps Zeng XZ et al Acta Pharmacologica Sinica npg as tartrate-resistant acid phosphatase (TRAP), cathepsin K, β3-Integrin and DC-STAMP [5] . During the differentiation of osteoclasts, the fusion of mononuclear pre-osteoclasts is a critical event during the formation of mature multinucleated osteoclasts [6] . Fusion failure can result in the severe reduction of bone-resorbing activity and an increase in bone mass, as seen in osteopetrosis [7] .…”
Section: Introductionmentioning
confidence: 99%